A study on kid mortality - focusing on nutritional myopathy - Silva Filipe; Pires Isabel (Veterinarski Glasnik)
Nutritional myopathy, or white muscle disease, is a common condition in livestock caused by deficiencies in selenium and vitamin E. This study aimed to investigate the incidence of nutritional myopathy in caprine kids, focusing on its role as a cause of mortality in the Trás-os-Montes region. A post-mortem study was conducted over one year on 111 young goats, less than three months old, originating from autochthonous breeds of Trás-os-Montes and Alto Douro (Bravia and Serrana breed). Necroscopy was performed to examine for macroscopic findings. Collected tissue was fixed in 10 % buffered formalin and examined histopathologically. Parasitological analysis was also performed. The clinical history, post-mortem lesions, and histological examination were used to establish cause of each kid’s death. The primary lesions were enteritis and pneumonia. The findings revealed that 22.5 % of the necropsied goats exhibited lesions consistent with nutritional myopathy, macroscopically detectable in the limb and heart muscles. The study underscores the importance of implementing preventive measures and nutritional management practices to mitigate the occurrence of nutritional myopathy in goat herds in Trás-os-Montes.